Teachers’ Collaboration Practices in Public Primary Schools in Tanzania: Evidence from Mwanza Region - Venant Fundi; Prisca Mbogo; Coletha Ngirwa (Universitas Nurul Jadid, 2026)
The study examined the extent of teachers’ collaborative practices in public primary schools in Tanzania using a convergent mixed-methods design grounded in Social Constructivism. The study population comprised 2,994 teachers across 218 primary schools, from which a sample of 352 respondents (including classroom teachers, academic teachers, head teachers, and key informants) was selected using Yamane’s formula. Participants were drawn from 44 schools across two districts to ensure proportional representation. Data were collected using questionnaires, interviews, and documentary review. Quantitative data were analyzed using descriptive statistics (mean, standard deviation, and skewness), while qualitative data were analyzed through content analysis. Findings indicate that teachers’ collaboration practices are generally high across the sampled schools, suggesting that a collaborative learning culture and professional interaction among teachers are well established. The results imply that existing school-based professional networks contribute positively to instructional coordination and shared pedagogical practices. The study carries important implications for education policy and school management. At the policy level, the government should strengthen workforce planning by rebalancing teacher distribution to address workload disparities that may undermine the quality of collaboration over time. At the managerial level, school leaders should institutionalize structured collaboration frameworks to sustain and further enhance professional cooperation among teachers, particularly in high-load teaching environments.